Research progress of hydrogels in the prevention of pelvic inflammatory disease - Yile Xiao; Teng Ma; Haoming Wu; Qiao Su; Yayu Zhou; Bingnan Zhou; Keyi Yang; Zhengguang Pu; Wanyue Feng; Xin Yong; Huili Zhu; Xulin Hu (MedComm – Biomaterials and Applications)
Abstract Pelvic inflammatory disease (PID) is a critical global health concern with the potential to lead to adverse outcomes, including infertility and chronic pelvic pain. Since PID is often caused by ascending vaginal infections or urinary tract infections, understanding the treatment of both is critical to preventing PID. Meanwhile, the emergence of drug‐resistant and persistently infected strains poses a growing challenge. This review discusses current clinical treatments for the prevention of PID from the physiologic basis of PID, as well as summarizes the advantages and research progress of hydrogels in the prevention of PID. In contrast to conventional treatments, hydrogels serve as excellent vehicles for vaginal drug delivery, maintaining the presence of the drug at the target site and controlling its release. In the context of urinary tract infections (UTIs), hydrogels are employed primarily as coatings on catheters to prevent and treat catheter‐associated UTIs. Finally, this review summarizes the limitations of hydrogels in PID prevention and future directions for development with the aim of elucidating avenues for clinical treatment of PID and informing further research.